Molten salt electro‐preparation of graphitic carbons - Fei Zhu; Jianbang Ge; Yang Gao; Shijie Li; Yunfei Chen; Jiguo Tu; Mingyong Wang; Shuqiang Jiao (Exploration, 2023)
Abstract Graphite has been used in a wide range of applications since the discovery due to its great chemical stability, excellent electrical conductivity, availability, and ease of processing. However, the synthesis of graphite materials still remains energy‐intensive as they are usually produced through a high‐temperature treatment (>3000°C). Herein, we introduce a molten salt electrochemical approach utilizing carbon dioxide (CO2) or amorphous carbons as raw precursors for graphite synthesis. With the assistance of molten salts, the processes can be conducted at moderate temperatures (700–850°C). The mechanisms of the electrochemical conversion of CO2 and amorphous carbons into graphitic materials are presented. Furthermore, the factors that affect the graphitization degree of the prepared graphitic products, such as molten salt composition, working temperature, cell voltage, additives, and electrodes, are discussed. The energy storage applications of these graphitic carbons in batteries and supercapacitors are also summarized. Moreover, the energy consumption and cost estimation of the processes are reviewed, which provides perspectives on the large‐scale synthesis of graphitic carbons using this molten salt electrochemical strategy.